Chemical composition dependent local lattice distortions and magnetism in high entropy alloys. (February 2021) - Tan, Yuan-Yuan; Su, Ming-Yao; Xie, Zhou-Can; Chen, Zhong-Jun; Gong, Yu; Zheng, Li-Rong; Shi, Zhan; Mo, Guang; Li, Yong; Li, Ling-Wei; Wang, Hai-Ying; Dai, Lan-Hong
Abstract: A distinguish feature of high-entropy alloys (HEAs) is well-defined crystalline structure with chemical disorder. While, local lattice distortion is a longstanding issue in HEAs and more challenging than traditional alloys. However, reports on local lattice distortion of HEAs are rarely related to chemical compositions. Here, we use synchrotron radiation facility based XRD and X-ray absorption fine structure (XAFS) to examine averaged lattice distortion and element specified local lattice distortions in CrCoNi medium-entropy alloy (MEA), CrFeCoNi and CrMnFeCoNi HEAs. The results showed that averaged lattice distortions observed from XRD patterns are subtle. The distortion magnitude centred around certain alloying element observed in XAFS spectra keeps in the same order, generally, Ni > Co > Fe > Cr > Mn. The observed positive strains are proposed to counteract negative strains and thus leading to observation of subtle averaged lattice distortion. The XANES results suggested that local electron structure flexibility of element might be one factor that contributes to local lattice distortions. The magnetic measurements indicated a paramagnetic state of all the studied alloys at ambient conditions. This study provides key information on local lattice distortion and its correlations with chemical compositions in HEAs, which is of crucial importance in tailoring properties of advanced HEAs and other multicomponent alloys. Graphical abstract: Image 1 Highlights: A method on quantitatively evaluating lattice distortion by a combination of XRD and XAFS in HEA was presented. XRD patterns present subtle averaged lattice distortions, but observe gradual lattice expansion with chemical complexity. XAFS spectra demonstrate element dependent local lattice distortion order of specific alloying element: Ni > Co > Fe > Cr > Mn. The magnetic measurements indicated a paramagnetic state of all the studied alloys at ambient conditions.